TikTok as a Venting Platform and Its Role in Encouraging Cyberbullying Among Generation Z - Shafira Azizah; Muaya Feriyana; Firmansyah Firmansyah (Universitas Islam Al-Azhar Mataram, 2026)
Cyberbullying has become a growing global issue alongside the rapid development of information technology and social media. Among Generation Z, the high intensity of social media use increases the risk of exposure to negative online interactions. One of the most popular platforms, TikTok, is not only used for entertainment but also as a medium for venting, where users express their emotions and personal experiences. While venting can provide emotional relief and social support, it also opens the possibility of negative responses such as harassment, body shaming, and hate speech. These interactions can significantly affect mental health, including increased anxiety, decreased self-confidence, and psychological distress. This study aims to analyze the relationship between venting activities on TikTok and the emergence of cyberbullying among Generation Z. Based on a review of relevant sources, the findings indicate that anonymity, rapid content dissemination through algorithms, and the culture of social validation are the main factors contributing to cyberbullying. Therefore, improving digital literacy, promoting ethical online behavior, and strengthening platform regulations are essential to create a safer and more supportive digital environment.